Substantial gaps in knowledge of Bordetella pertussis antibody and T cell epitopes relevant for natural immunity and vaccine efficacy - Vaughan, Kerrie (Hum Immunol, 2014)
The recent increase in whooping cough in vaccinated populations has been attributed to waning immunity associated with the acellular vaccine. The Immune Epitope Database (IEDB) is a repository of immune epitope data from the published literature and includes T cell and antibody epitopes for human pathogens. The IEDB conducted a review of the epitope literature, which revealed 300 Bordetella pertussis-related epitopes from 39 references. Epitope data are currently available for six virulence factors of B. pertussis: pertussis toxin, pertactin, fimbrial 2, fimbrial 3, adenylate cyclase and filamentous hemagglutinin. The majority of epitopes were defined for antibody reactivity; fewer T cell determinants were reported. Analysis of available protective correlates data revealed a number of candidate epitopes; however few are defined in humans and few have been shown to be protective. Moreover, there are a limited number of studies defining epitopes from natural infection versus whole cell or acellular/subunit vaccines. The relationship between epitope location and structural features, as well as antigenic drift (SNP analysis) was also investigated. We conclude that the cumulative data is yet insufficient to address many fundamental questions related to vaccine failure and this underscores the need for further investigation of B. pertussis immunity at the molecular level.